Factors influencing Whooper Swan Cygnus cygnus numbers on the Isle of Tiree, Argyll, Scotland - Bowler, John (Wildfowl, 2021)
Annual peak counts of Icelandic Whooper Swans Cygnus cygnus on the mesotrophic lochs of the Isle of Tiree in winters 2001/02–2020/21 varied between 106 and 502 birds in autumn and between 45 and 186 in January, with no significant trends over time. Swans were present in nationally important and sometimes internationally important numbers at Loch a’ Phuill during 2001–2018 but counts dropped below the 1% threshold of nationally important numbers when this figure was revised upwards in 2019. Peak numbers of swans in both autumn and winter were significantly negatively correlated with recent rainfall. Periods of dry weather reduced loch levels by up to 0.5 m, which improved the swans’ access to submerged macrophyte food supplies. A significant positive correlation between summer rainfall and peak autumn counts implied that autumn macrophyte food supplies were lower after dry summers, in which large parts of the lochs dried out completely. The annual proportion of cygnets recorded ranged from 5.6% to 29.9% and did not differ significantly from the rest of the UK. The proportion of cygnets did not correlate with peak swan numbers in either autumn or January, reinforcing the view that variation in swan numbers on the island was affected by external factors such as food supply, rather than annual variation in demographics.